"MODERN ASPECTS OF PREDICTION AND EARLY DIAGNOSIS OF CEREBROVASCULAR DISORDERS IN PREECLAMPSIA" - Shamsieva Tursunoy (Zeta Repository, 2023)
Preeclampsia (PE) is a serious medical and social problem throughout the world, as it remains one of the main causes of perinatal and maternal mortality. In accordance with the goals and objectives of the work, a survey of 140 women will be conducted.